Azure remote compute for VSCode. (Pragmatic AI Solutions, 2022)
Step up your local setup by setting a remote compute instance with attached SMB storage and then connect your local VSCode editor so that you can execute code and Jupyter Notebooks remotely. In this video I go through everything you need to know to crete a compute instance in Azure, both in Azure Machine Learning Studio and using the Data Science Virtual Machine spot instance that allows you to save costs when running a high memory with GPU instance. Because remote compute instances in the cloud should be considered ephemeral, specially if you are using spot instances, this video also covers setting up a storage account and a file share configuration for a Samba share that allows you to attach that same storage to any compute. Topics include: Create an Azure compute instance Learn about Spot Instances and other cost savings Setup VSCode for remote code execution Create an SMB file share and attach it to a VM Execute Jupyter Notebooks remotely Useful links: * Github Repository with summary instructions * Create a File share documentation on Azure * Data Science VMs in Azure.